Content Analysis of Www.Myjoyonline.Com and Www.Graphic.Com.Gh Coverage of the 2016 General Elections of Ghana - Ofori, R.A. (University of Ghana, 2019)
This study content analyzed the January 2016 to January 2017 articles relating to the 2016 general elections in Ghana that appeared on two news portals - myjoyonline.com and graphic.com.gh. The objectives of the study were to identify the dominant frames that were used by the two online portals in covering the elections as well as the level of prominence attached to the election coverage. It also sought to find out the level of bias in their coverage. A quantitative content analysis of the two news portals was carried out. A total of 216 stories were collected. The framing theory was used to support the study. The findings of the study showed that, the two media outlets framed most of their election stories on the “electoral issues”, “economy” and “peace” frame. Additionally, the two news portals studied were neutral in the manner in which they covered the 2016 general elections. Again, prominence was placed on the election stories. Most of the news published were straight news pieces and were accompanied by photographs.
MA. Communication Studies
Keywords: Content Analysis; Elections; Myjoyonline; Graphic